2005
DOI: 10.2337/diacare.28.3.658
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Prevalence of Limited Joint Mobility in Type 1 Diabetes in a U.K. Clinic Population Over a 20-Year Period

Abstract: OBJECTIVE -Limited joint mobility (LJM), one of the earliest clinically apparent long-term complications of type 1 diabetes, is a risk marker for subsequent microvascular complications. We hypothesize that the prevalence of LJM may have decreased during the past two decades due to improved standards of glycemic control. RESEARCH DESIGN AND METHODS -A single observer performed a survey in 204consecutive patients with type 1 diabetes (106 men and 98 women, age 27 Ϯ 1 years, HbA 1c 8.3 Ϯ 0.1%, duration of diabete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
2
10

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 20 publications
2
42
2
10
Order By: Relevance
“…Limited joint mobility, another proposed marker of tissue glycation, has been associated with microvascular disease in adolescents (6,16,17); however, the prevalence of this abnormality was low in our cohort. This finding is in keeping with recent data from the U.K. (8) and suggests that PFT is a more sensitive measure of tissue glycation.…”
Section: Baselinesupporting
confidence: 80%
See 1 more Smart Citation
“…Limited joint mobility, another proposed marker of tissue glycation, has been associated with microvascular disease in adolescents (6,16,17); however, the prevalence of this abnormality was low in our cohort. This finding is in keeping with recent data from the U.K. (8) and suggests that PFT is a more sensitive measure of tissue glycation.…”
Section: Baselinesupporting
confidence: 80%
“…In particular, measurement of collagen glycation obtained by skin biopsy is invasive and not applicable in routine clinical care. Limited joint mobility in the hands has been previously described as an index of tissue glycation, but its prevalence has fallen significantly in the past two decades (8). Ultrasound has recently been used to detect thickening of the plantar aponeurosis, a tissue rich in collagen and susceptible to nonenzymatic glycation, in adults with type 1 and type 2 diabetes (9,10).…”
mentioning
confidence: 99%
“…Some authors have showed that there is a clear link between upper limb musculoskeletal abnormalities and poor metabolic control (Ramchurn et al, 2009). It has been observed a reduction in frequency of LJM between the mid-70s and mid-90s in children, most likely due to the improved glucose control during this era (Infante et al, 2001;Lindsay et al, 2005).…”
Section: Type 1 Diabetes and Limited Joint Mobilitymentioning
confidence: 99%
“…With rare exception, LJM appears after the age of 10 years. The prevalence of LJM in T1D, evaluated in several studies ranges from 9 to 58% in paediatric and adult patients (Lindsay et al, 2005). The biochemical basis of LJM may be a consequence of changes in the connective tissue, probably due to alterations in the structural macromolecules of the extracellular matrix.…”
Section: Type 1 Diabetes and Limited Joint Mobilitymentioning
confidence: 99%
“…Unclear; limited evidence, only 1 study identified (Lindsay et al, 2005) Unclear; limited evidence, only 1 study identified (Lindsay et al, 2005) No Insufficient evidence that effective diabetes management reduces the risk of Type 1 diabetes mellitus Myopia Unclear; limited evidence, only 1 study identified (Jacobsen et al, 2008) Unclear; limited evidence, only 1 study identified (Jacobsen et al, 2008) No Insufficient evidence that effective diabetes management reduces the risk of Type 1 diabetes mellitus…”
Section: Limited Joint Mobilitymentioning
confidence: 99%